Reactualizing Ma‘rifah and Fanā’: A Sufi Spiritual Path for Addressing the Existential Crisis of Modern Society - Zakariyah, Zakariyah; Muttaqin, Ainul (Dirasah International Journal of Islamic Studies, 2025)
Modernity, characterized by rationalism, materialism, and the dominance of technology, has generated spiritual, moral, and existential crises in contemporary human life. This condition highlights the need to reinterpret Sufi teachings so that they remain relevant in addressing modern challenges. This study aims to analyze the concepts of ma‘rifah and fanā’ in the classical Sufi tradition and examine their reinterpretation within the framework of modern Sufism. This research employs a qualitative approach through library research, examining both classical and contemporary literature related to Sufi thought. The findings reveal that in classical Sufism, ma‘rifah is understood as an inner knowledge of God attained through spiritual purification and mystical experience, while fanā’ refers to the dissolution of the human ego in the presence of the Divine without negating adherence to Islamic law (sharia). In the context of modern Sufism, these two concepts have undergone a contextual reinterpretation. Ma‘rifah is no longer viewed solely as an individual mystical experience but as a form of spiritual awareness integrated with rationality, ethics, and social responsibility. Meanwhile, fanā’ is interpreted as the transformation of ego-centered consciousness into an ethical awareness that fosters social concern and moral commitment. This reinterpretation demonstrates that Sufism is not incompatible with modernity; rather, it can serve as a spiritual and ethical foundation for addressing the crisis of meaning in modern society. Therefore, the concepts of ma‘rifah and fanā’ in modern Sufism function as a spiritual paradigm capable of balancing the material and spiritual dimensions of contemporary human life..